Manual de ventilação mecânica no Paciente queimado - Ribeiro, Helena Cristina Caetano [UNIFESP] (2019)
Introduction: Acute burns represent a public health problem in Brazil, with high morbidity and mortality. Pulmonary complications occur most often in the presence of severe inhalation lesions, but may also develop in their absence. Focused clinical practice decreases risk of iatrogenic complications, however there is shortage of educational materials focused on mechanical ventilation for patients with acute burns. Objective: To develop, validate and publish a manual of mechanical ventilation in burn patients. Method: Study was developed in five stages. In the first step, an Internet search was performed. Next, literature review was conducted. In the third step, an online interview with the target audience of the manual was conducted. In the fourth step, the manual was developed and validated with the Delphi technique. Finally, the International Standard Book Number was requested. Results: The "Handbook of Mechanical Ventilation in Patients with Acute Burns: Recommendations and Suggestions" is comprised of 11 chapters. It was validated by specialists in the field, with 94.3% absolute agreement among the evaluators. Conclusion: The “Handbook of Mechanical Ventilation in Patients with Acute Burns: Recommendations and Suggestions” in printed and digital formats (e-book) was developed, validated and published.